2014
DOI: 10.1096/fj.14-254359
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzae increases the susceptibility and inflammatory response of airway epithelial cells to viral infections

Abstract: Nontypeable Haemophilus influenzae (NTHI), a common colonizer of lungs of patients with chronic obstructive pulmonary disease (COPD), can enhance expression of the cellular receptor intercellular adhesion molecule 1 (ICAM-1), which in turn can be used by major group human rhinoviruses (HRVs) for attachment. Here, we evaluated the effect of NTHI-induced up-regulation of ICAM-1 on viral replication and inflammatory responses toward different respiratory viruses. Therefore, human bronchial epithelial cells were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 57 publications
(80 reference statements)
5
61
0
Order By: Relevance
“…Exposure of respiratory epithelial cells to H. influenzae increases the expression of ICAM-1, the main receptor for major group HRV. By doing so, the bacteria increase viral binding and replication of this type of virus in vitro (Gulraiz et al, 2015;Sajjan et al, 2006). Moreover, we have recently shown that H. influenzae and RSV can synergize in inducing the release of pro-inflammatory cytokines by respiratory epithelial cells (Bellinghausen et al, 2016).…”
Section: Bacterial Pathogens Influencing the Response To Viral Infectionmentioning
confidence: 99%
“…Exposure of respiratory epithelial cells to H. influenzae increases the expression of ICAM-1, the main receptor for major group HRV. By doing so, the bacteria increase viral binding and replication of this type of virus in vitro (Gulraiz et al, 2015;Sajjan et al, 2006). Moreover, we have recently shown that H. influenzae and RSV can synergize in inducing the release of pro-inflammatory cytokines by respiratory epithelial cells (Bellinghausen et al, 2016).…”
Section: Bacterial Pathogens Influencing the Response To Viral Infectionmentioning
confidence: 99%
“…It has been shown in vitro or in vivo (using the cotton rat model) that treatment with S. pneumoniae prior to RSV challenge results in enhanced RSV replication (200). The increased RSV replication is also observed in vitro after pretreatment with heat-inactivated H. influenzae (201). Additionally, lipopolysaccharide (LPS; Gram-negative bacterial cell wall component) exposure results in a Th2 immune polarization and increased severity during subsequent RSV challenge (197).…”
Section: Rsv and Bacterial Colonizationmentioning
confidence: 99%
“…pathobiont presence enhancing viral acquisition and replication, might also occur: for example, H. influenzae has been shown to induce expression of ICAM-1 and TLR3-receptors, which enhanced rhinovirus binding and stimulated rhinovirus-induced chemokine production [147]. Furthermore, a recent in vitro study has shown that H. influenzae similarly increases viral replication of respiratory syncytial virus, which was related to the release of proinflammatory cytokines IL-6 and IL-8, suggesting specific bacterial community members can aggravate (inflammatory response to) viral infection [148]. Furthermore, pre-incubation of human bronchial epithelial cells with S. pneumoniae leads to increased susceptibility to infection with human metapneumovirus (figure 2d) [149].…”
Section: Pathogenesis Of Respiratory Infections: the Ecosystem Perspementioning
confidence: 99%